Antigen presentation by clonally diverse CXCR5+ B cells to CD4 and CD8 T cells is associated with durable response to immune checkpoint inhibitors - Ding, Lizhong; Sun, Lu; Bu, Melissa T.; Zhang, Yanjun; Scott, Lauren N.; Prins, Robert M.; Su, Maureen A.; Lechner, Melissa G.; Hugo, Willy (Frontiers in Immunology, 2023)
Tumors from melanoma patients who responded to ICI (immune checkpoint inhibitor) or MAPK pathway inhibitor (MAPKi) therapy generally displayed increased T cell infiltration and interferon gamma (IFNγ) pathway activation. Yet, the rate of durable tumor control after ICI is almost twice that of MAPKi. We discovered response to ICI is associated with CXCL13-driven recruitment of CXCR5+ B cells with significantly higher clonal diversity than MAPKi. Our in vitro data indicate that CXCL13 production was increased in human peripheral blood mononuclear cells by anti-PD1, but not MAPKi, treatment. Higher B cell infiltration and B cell receptor (BCR) diversity allows presentation of diverse tumor antigens by B cells, resulting in activation of follicular helper CD4 T cells (Tfh) and tumor reactive CD8 T cells after ICI therapy. Higher BCR diversity and IFNγ pathway score post-ICI are associated with significantly longer patient survival compared to those with either one or none. Thus, response to ICI, but not to MAPKi, depends on the recruitment of CXCR5+ B cells into the tumor microenvironment and their productive tumor antigen presentation to follicular helper and cytotoxic, tumor reactive T cells. Our study highlights the potential of B cell-based cancer vaccine to enhance the rate of durable ICI response.